2013
DOI: 10.1149/05007.0241ecst
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Different Nano Scale Energetic Material Systems for Reactive Wafer Bonding

Abstract: This paper introduces a method that uses a specific form of local heat generation, which is based on nano scale reactive multilayer systems. Such systems consist of several layers of minimum two different materials with nano scale thicknesses. These layers generate heat based on a self-propagating exothermic reaction during their intermixing. The resulting heat can be used as heat source for bonding processes at chip and wafer-level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…For example, Braeuer et al utilized 1.6-μm thick Pd/Al multilayers to join Si dies and wafers [143]. This highly exothermic pair was sputter deposited onto Si with a bilayer thickness of~180 nm, coated with a Sn capping layer, and pressed to a mating Si piece.…”
Section: Joiningmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Braeuer et al utilized 1.6-μm thick Pd/Al multilayers to join Si dies and wafers [143]. This highly exothermic pair was sputter deposited onto Si with a bilayer thickness of~180 nm, coated with a Sn capping layer, and pressed to a mating Si piece.…”
Section: Joiningmentioning
confidence: 99%
“…When ignited, this multilayer provided a sufficient amount of heat to melt and flow the Sn overlayer. The joined assemblies exhibited good adhesion strengths,~77 ± 5 MPa, and cracks were not observed in either the PdAl or Sn layers [143]. Continued research into solder-based processes seeks solutions for fabricating hermetic seals, with leak rates b10 − 10 atm cm 3 s − 1 [222,223,244].…”
Section: Joiningmentioning
confidence: 99%
See 1 more Smart Citation
“…These examples consider the reactive multilayered laminates. That is, the dual-bath ECD technique was used by Braeuer et al [79], and since aluminum deposition at room temperature with a water-based electrolyte is challenging, the less energetic pairs Pd/Zn and Pd/Sn were synthesized. The authors reported that even the order of layers is important: deposition of Zn on Pd is possible, while a reverse configuration results in randomized surfaces due to etching of the Zn layer by the Pd-based electrolyte.…”
Section: Electrical Methods (Electrochemical Electrodynamic and Elementioning
confidence: 99%
“…The limitations include difficulties in the selection of components and electrolytes, potential surface reactions during transfer from one bath to another, and possible displacement reactions. Potential developments include the utilization of a single-bath ECD technique [79] and the use of ionic liquid-based electrolytes instead of water-based electrolytes [59,81].…”
Section: Electrical Methods (Electrochemical Electrodynamic and Elementioning
confidence: 99%